2012
DOI: 10.5942/jawwa.2012.104.0037
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide assessment of nitrosamine occurrence and trends

Abstract: Nitrosamine data reported from the first rounds of samples collected under the second Unregulated Contaminants Monitoring Rule (UCMR2) and the Ontario Drinking Water Surveillance Program were reviewed to assess the frequency and magnitude of occurrence and the effect of disinfectant type and other treatment factors on reported nitrosamine concentrations. Initial monitoring data reveal that N‐nitrosodimethylamine (NDMA) was detected in drinking water at concentrations higher than the UCMR2 minimum reporting lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 32 publications
2
62
1
Order By: Relevance
“…Different types of nitrosamines in finished waters have been detected and characterized in several other locations in North America, the United Kingdom, Australia, and Asia. In these studies, NDMA was the most commonly detected, and the concentrations were up to 18.3 ng/L in North America, up to 65 ng/L in Canada (Russell et al, 2012;Krasner et al, 2013;Uzun et al, 2015;Charrois et al, 2007;Zhao et al, 2008), up to 10 ng/L in Japan (Asami et al, 2009), and up to 35.7 ng/L in China (Wang et al, 2010(Wang et al, , 2012. Compared to those surveys, NDEA and NDBA were also two dominant nitrosamines in finished waters in this study and previous reports of China (Wang et al, 2010(Wang et al, , 2012.…”
Section: Occurrence Of Multiple Nitrosamines In Source Water and Finimentioning
confidence: 61%
“…Different types of nitrosamines in finished waters have been detected and characterized in several other locations in North America, the United Kingdom, Australia, and Asia. In these studies, NDMA was the most commonly detected, and the concentrations were up to 18.3 ng/L in North America, up to 65 ng/L in Canada (Russell et al, 2012;Krasner et al, 2013;Uzun et al, 2015;Charrois et al, 2007;Zhao et al, 2008), up to 10 ng/L in Japan (Asami et al, 2009), and up to 35.7 ng/L in China (Wang et al, 2010(Wang et al, , 2012. Compared to those surveys, NDEA and NDBA were also two dominant nitrosamines in finished waters in this study and previous reports of China (Wang et al, 2010(Wang et al, , 2012.…”
Section: Occurrence Of Multiple Nitrosamines In Source Water and Finimentioning
confidence: 61%
“…With more utilities switching from free chlorine to chloramine as the secondary disinfectant, NDMA has been detected in many chloraminated drinking water systems across North America (Blute et al, 2010;Russell et al, 2012). Most of the time the reported NDMA concentrations have been below 10 ng/L; only a small portion of the samples have shown higher concentrations (Russell et al, 2012). At the time of writing, NDMA has been mainly regulated at regional levels.…”
Section: Introductionmentioning
confidence: 92%
“…Most studies have found that NDMA is rather associated with chloramination than with chlorination (4)(5)(6). Systems with high plant effluent NDMA (i.e., >50 ng/L) typically use chloramines as the primary rather than secondary disinfectant (6), reflecting the potential for precursor deactivation by strong pre-oxidants such as chlorine.…”
Section: Introductionmentioning
confidence: 98%